Vagrant writing : social and semiotic disorders in the English renaissance - Taylor, Barry (Theory/culture series, 1991)
Vagrant Writing addresses the semiotic dimension of social change in Renaissance England. Barry Taylor explores what happens to Tudor and Jacobean practices of writing when the ideology of the Word which underpins them must interpret, regulate and contain a social order undergoing radical transformation.